2018
DOI: 10.1021/acs.jmedchem.8b01326
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Time-Dependent Inhibition (TDI) of Cytochrome P450 3A4 (CYP3A4) Resulting from Bioactivation of a Fluoropyrimidine Moiety

Abstract: Herein we describe structure−activity relationship (SAR) and metabolite identification (Met-ID) studies that provided insight into the origin of time-dependent inhibition (TDI) of cytochrome P450 3A4 (CYP3A4) by compound 1. Collectively, these efforts revealed that bioactivation of the fluoropyrimidine moiety of 1 led to reactive metabolite formation via oxidative defluorination and was responsible for the observed TDI. We discovered that substitution at both the 4-and 6positions of the 5-fluoropyrimidine of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Additional structure–liability studies confirmed that dual substitution at the 4- and 6-positions of the 5-fluoropyrimidine ring was sufficient to ameliorate the TDI. This protective effect was exemplified by the 4,6-dimethyl-5-fluoropyrimidine analogue 465 , which demonstrated 10-fold weaker inhibition of CYP3A4 relative to 464 …”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional structure–liability studies confirmed that dual substitution at the 4- and 6-positions of the 5-fluoropyrimidine ring was sufficient to ameliorate the TDI. This protective effect was exemplified by the 4,6-dimethyl-5-fluoropyrimidine analogue 465 , which demonstrated 10-fold weaker inhibition of CYP3A4 relative to 464 …”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
“…This adduct would lose HF to afford 466 , which would then tautomerize to the observed product 467 . Alternatively, epoxide ring opening with loss of fluoride, as the result of anchimeric assistance by the pyrrolidine N atom, would produce a highly electrophilic quinone iminium derivative that could either add GSH to produce 467 or be reduced to give 468 . Further support for this postulate was provided by studies of the fluorophenyl and unsubstituted pyrimidine analogues, neither of which resulted in CYP3A4 TDI (IC 50 > 30 μM).…”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
“…The bioactivation of fluoropyrimidine is a rare occurrence and is contrary to documented cases that show that adding fluorine and nitrogen to aromatic rings can slow P450 metabolism. ,, Some fluoropyrimidine-containing compounds were being developed as BACE1 inhibitors 14 for the treatment of Alzheimer’s disease . The molecules investigated were found to have time-dependent inhibition (TDI) of CYP 3A4, a predominant P450 enzyme, indicating an increased potential for drug–drug interactions in the clinic .…”
Section: Aromatic Bioactivationmentioning
confidence: 99%
“…62 Of note, the relative importance of the corresponding structural features was correctly recognized (Figure 6b). Additional examples [63][64][65] are provided in the Supporting Data and the accompanying code repos-…”
Section: Pharmacophore Motif Recognitionmentioning
confidence: 99%